THE DETERMINATION OF DAWN TIME IN MEDAN USING SQM WITH RASPBERRY PI BASED - Putraga, Hariyadi; Rakhmadi, Arwin Juli; Hidayat, Muhammad; Firdaus, Muhammad Dimas (Proceeding International Seminar of Islamic Studies, 2023)
The beginning of dawn prayer is still a hot debate among Falak practitioners and astronomers in Indonesia. The Adzan marks the start of dawn prayer time were too fast because the sky is still dark and not as mentioned in the Hadith, which is when the sky gets brighter.  This study aims to prove the change from the night sky to the bright sky using a photometer called SQM with a recording device based on Raspberry Pi so that it can be used easily, quickly, lightly, and also safe to be left in a location during the data collection process. The results obtained in this study show that SQM on Raspberry can function properly, the dawn time at SQM readings using Raspberry Pi shows that the Sun is in the dip range of 15-18 degrees below the horizon when the sky changes brighter occurred